2020
DOI: 10.1021/acs.biochem.0c00096
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Cj1427, an Essential NAD-Dependent Dehydrogenase for the Biosynthesis of the Heptose Residues in the Capsular Polysaccharides of Campylobacter jejuni

Abstract: Many strains of Campylobacter jejuni display modified heptose residues in their capsular polysaccharides (CPS). The precursor heptose was previously shown to be GDP-d-glycero-α-d-manno-heptose, from which a variety of modifications of the sugar moiety have been observed. These modifications include the generation of 6-deoxy derivatives and alterations of the stereochemistry at C3–C6. Previous work has focused on the enzymes responsible for the generation of the 6-deoxy derivatives and those involved in alterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 40 publications
1
48
0
Order By: Relevance
“…jejuni NCTC 11168 is composed of 35 genes, as illustrated in Figure S1 . Previous investigations have functionally characterized the genes necessary for the biosynthesis of the d -glycero- l -gluco-heptose moiety and modification (Cj1152, Cj1423, Cj1424, Cj1425, Cj1427, Cj1428, and Cj1430). In addition, the enzymes Cj1415, Cj1416, Cj1417, and Cj1418 have been shown to be required for the biosynthesis of the phosphoramidate modification, and gene knockout experiments have identified the enzymes (Cj1422 and Cj1421) required for the transfer of the phosphoramidate modifications to specific sugar receptors. , More recently, we have shown that Cj1441 is required for the conversion of uridine diphosphate (UDP)-glucose to UDP-glucuronate and that this enzyme is unable to catalyze the formation of an amide bond via the attack of an amine substrate with the putative thioester intermediate formed during the oxidation of UDP-glucose . The enzymes required for the biosynthesis of the two amines (serinol and ethanolamine) found in the HS:2 capsule are currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…jejuni NCTC 11168 is composed of 35 genes, as illustrated in Figure S1 . Previous investigations have functionally characterized the genes necessary for the biosynthesis of the d -glycero- l -gluco-heptose moiety and modification (Cj1152, Cj1423, Cj1424, Cj1425, Cj1427, Cj1428, and Cj1430). In addition, the enzymes Cj1415, Cj1416, Cj1417, and Cj1418 have been shown to be required for the biosynthesis of the phosphoramidate modification, and gene knockout experiments have identified the enzymes (Cj1422 and Cj1421) required for the transfer of the phosphoramidate modifications to specific sugar receptors. , More recently, we have shown that Cj1441 is required for the conversion of uridine diphosphate (UDP)-glucose to UDP-glucuronate and that this enzyme is unable to catalyze the formation of an amide bond via the attack of an amine substrate with the putative thioester intermediate formed during the oxidation of UDP-glucose . The enzymes required for the biosynthesis of the two amines (serinol and ethanolamine) found in the HS:2 capsule are currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we showed that Cj1427 was functionally able to catalyze the conversion of GDP- d - glycero -α- d - manno -heptose ( 1 ) to GDP- d - glycero -4-keto-α- d - lyxo -heptose ( 2 ) . We showed that the isolated Cj1427 contained a tightly bound NADH cofactor with an occupancy of 85%. , Additionally, we showed that Cj1427 does not exchange the bound cofactor during catalytic turnover, but required an α-keto acid cosubstrate, preferably α-ketoglutarate, to reoxidize the bound NADH to NAD + such that Cj1427 could catalyze the oxidation of GDP- d - glycero -α- d - manno -heptose ( 1 ) to GDP- d - glycero -4-keto-α- d - lyxo -heptose ( 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cofactors bound to Cj1428 were determined by FPLC anion exchange chromatography. The FPLC methodology used was outlined previously . Briefly, concentrated Cj1428 (1.0 mM) was diluted with water to a final concentration of 400 μM and then heat-denatured (95 °C for 60 s) to liberate the bound cofactor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Ddah pathway, the initiating C4, C6 dehydratase DdahA creates the 4-keto function and is specific for the C7 sugar ( 2 , 4 ). The initiating C4 oxidase for the Mlgh pathway MlghA was recently identified as Cj1427 (formerly WcaG), which requires α-ketoglutarate to support its activity on GDP- manno -heptose ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%